The Alysiinae (Hym., Braconidae) parasites of the Agromyzidae (Diptera). II. The parasites of Agromyza Fallén. - Griffiths, Graham C. D. (Contributions to Entomology = Beiträge zur Entomologie, 1966)
1. This paper, the second of a series, deals with the Alysiinae parasites of Agromyza Fallen in Europe. These belong to four genera of the Dacnusini (Exotela, Dacnusa, Chorebus and Protodacnusa) and two non-Dacnusine genera, Dapsilarthra and Grandia. Protodacnusa has already been treated in the previous paper (Griffiths, 1964). - 2. The majority of the Dacnusini bred from Agromyza exhibit monophagy of the first or second degree and it is considered that host specialisation has played an important part in the speciation of the group. However Dapsilarthra spp. have more extensive host-ranges, none being confined to Agrowyza. Grandia is represented by the single known species attacking Agromyza apfelbecki Strobl. - 3. The genus Agromyza is unlikely to be monophyletic and has been provisionally divided into four main groups for the purposes of this paper. Keys to the Dacnusini parasites of each of these groups are given. - 4. The host/parasite lists produced in this paper are intended to be complete and to supersede previously published lists for Europe. - 5. Seven new species are described, five in Chorebus and two in Exotela. Nomenclatural Acts baeticus Griffiths, 1966 (Chorebus), spec. n. bres (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa bres credne (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa credne deione (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa deione eros (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa eros groschkei Griffiths, 1966 (Chorebus), spec. n. hilaris Griffiths, 1966 (Chorebus), spec. n. knautiae Griffiths, 1966 (Chorebus), spec. n. lar (Morley, 1924) (Chorebus), comb. n. hitherto Dacnusa lar lugubris (Nixon, 1937) (Chorebus), comb. n. hitherto Dacnusa lugubris ninella (Nixon, 1945) (Chorebus), comb. n. hitherto Dacnusa ninella perkinsi (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa perkinsi pione (Nixon, 1944) (Chorebus), comb. n. hitherto Dacnusa pione polygoni Griffiths, 1966 (Chorebus), spec. n. resa (Nixon, 1937) (Chorebus), comb. n. hitherto Dacnusa resa rotundiventris (Thomson, 1895) (Chorebus), comb. n. hitherto Dacnusa (Dacnusa) rotundiventris solstitialis (Stelfox, 1952) (Chorebus), comb. n. hitherto Dacnusa solstitialis thisbe (Nixon, 1937) (Chorebus), comb. n. hitherto Dacnusa thisbe dryas (Nixon, 1948) (Dacnusa), comb. n. hitherto Rhizarcha dryas laeta (Nixon, 1954) (Dacnusa), comb. n. hitherto Pachysema laeta lissos (Nixon, 1954) (Dacnusa), comb. n. hitherto Pachysema lissos maxima (Fischer, 1961) (Dacnusa), comb. n. hitherto Pachysema maxima arunci Griffiths, 1966 (Exotela), spec. n. hera (Nixon, 1937) (Exotela), comb. n. hitherto Dacnus hera nowakowskii Griffiths, 1966 (Exotela), spec. n. phryne (Nixon, 1954) (Exotela), comb. n. hitherto Toxelea phryne